Whole exome sequencing reveals novel variants associated with diminished ovarian reserve in young women - Li, Na; Xu, Wanxue; Liu, Huimin; Zhou, Rui; Zou, Siqi; Wang, Shiqing; Li, Siyu; Yang, Zexin; Piao, Yongjun; Zhang, Yunshan (Frontiers in Genetics, 2023)
Background: Diminished ovarian reserve is one of the most important causes of female infertility. In the etiology study of DOR, besides age, it is known that chromosomal abnormality, radiotherapy, chemotherapy and ovarian surgery can result in DOR. For young women without obvious risk factors, gene mutation should be considered as a possible cause. However, the specific molecular mechanism of DOR has not been fully elucidated. Methods: In order to explore the pathogenic variants related to DOR, twenty young women under 35 years old affected by DOR without definite factors damaging ovarian reserve were recruited as the research subjects, and five women with normal ovarian reserve were recruited as the control group. Whole exome sequencing was applied as the genomics research tool. Results: As a result, we obtained a set of mutated genes that may be related to DOR, where the missense variant on GPR84 was selected for further study. It is found that GPR84Y370H variant promotes the expression of proinflammatory cytokines (TNF-α, IL12B, IL-1β) and chemokines (CCL2, CCL5), as well as the activation of NF-κB signaling pathway. Conclusion: In conclusion, GPR84Y370H variant was identified though analysis for WES results of 20 DOR patients. The deleterious variant of GPR84 could be the potential molecular mechanism of non-age-related pathological DOR through its role in promoting inflammation. The findings of this study can be used as a preliminary research basis for the development of early molecular diagnosis and treatment target selection of DOR.